Behavior of Steel–Lightweight Self Compacting Concrete Composite Beams with Various Degrees of Shear Interaction - Bayadir Abed Hadi; Samoel Mahdi Saleh (Civil Engineering Journal, 2023)
This study investigated the use of lightweight self-compacting concrete (LWSCC), which represents a trend in producing high-performance concrete, as slabs in steel-concrete composite beams with headed studs as shear connectors. Three push-out test specimens were fabricated and tested to assess the shear strength and behavior of M16-headed stud connectors embedded in LWSCC. Based on the push-out test results, six steel-LWSCC composite beams were manufactured and tested as simply supported composite beams. In addition, a steel-normal weight self-compacting concrete (NWSCC) composite beam specimen with full shear interaction was manufactured and tested for comparison. The main variables taken into account in this study were the degree of shear interaction and regions of bending moment (sagging or hogging). It was observed that the increase in degree of shear interaction from 50 to 100% improved the ultimate carrying capacity, the service load, and the stiffness of the tested steel-LWSCC beam specimens by a ratio reached to 96, 95, and 122%, respectively, when subjected to sagging bending moments and by a ratio reached to 57, 59, and 134%, respectively, when subjected to hogging bending moments. In addition, it was noted that the deflection and the end slip values for steel-LWSCC specimens under a sagging bending moment are smaller than those under a hogging bending moment, which have the same degree of shear interaction and at the same load level. Moreover, the experimental results show that the ultimate carrying capacity, service load, and stiffness values for the steel-NWSCC composite beam were higher than those for the steel-LWSCC beam specimens that have the same properties, while the ultimate deflection and end slip were smaller. Doi: 10.28991/CEJ-2023-09-11-04 Full Text: PDF